The Priority of Constraints Handling and Policy Program on Sustainable Management of Mangrove Forest Ecosystem in Langsa City, Aceh Province, Indonesia - Iswahyudi Iswahyudi; Cecep Kusmana; Aceng Hidayat; Bambang Pramudya Noorachmat (Sekolah Pascasarjana Universitas Brawijaya, 2019)
Management of mangrove ecosystems in Langsa City involves various stakeholders who have respectively different interests which encounter various obstacles and challenges in its implementation as well. In order to realize the sustainable management of mangrove forest ecosystems, it needs innovative and effective programs. The programs are expected toÂ encourage changes to the right direction. This study was designed to formulate the structure and classify the obstacles and policy programs in management of mangrove ecosystems based on their sub-elements. Data analysis used Interpretative Structural Modeling (ISM) method. The result shows that the key to the conservation of mangrove forests in Langsa City is the lack of community understanding about mangrove forest management, low community participation in mangrove forest rehabilitation and lack of government support in mangrove forest management programs. Meanwhile the key to policy program in managing mangrove ecosystems in Langsa City is the integrated management of mangrove forests.